Cognitive development Respiratory Tract Illness and Effects of eXposure (CORTEX) project: Data processing challenges in combining high spatial resolution pollution level data with individual level health and education data. (2018) - Lyons, Jane; Mizen, Amy; Rodgers, Sarah; Berridge, Damon; Akbari, Ashley; Wilkinson, Paul; Milojevic, Ai; Doherty, Ruth; Dearden, Lorraine; Lake, Iain; Carruthers, David; Strickland, Sarah; et al.
No abstract available